The effects of a pre-exercise feeding with or without fungal carbohydrases (carbogenTM) on blood parameters and exercise performance in elite cyclists: A preliminary study - Lewis Frank, L.; Baer, J. T.; Lambert, C. P.; Anderson, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
The effect of fungal carbohydrases (CarbogenTM [C]) consumed with a meal replacement bar (MBR) on glucose metabolism and exercise performance was determined in 5 male competitive cyclists. After a 12-hour fast, subjects performed two 60-min cycling bouts at 80% VO2max followed by a time-to-exhaustion (TE) ride at 100% VO2max. One hour prior to each cycling bout, subjects ingested a MRB + 160-mg C or 160-mg CaCO3 placebo (PL) in a double-blind, counterbalanced fashion. Blood was drawn for determination of glucose, insulin, and lactate at: fasting, 1 hour post-feeding, minutes 30 and 60 of exercise, and after TE. Two-way ANOVA revealed a significant (p < .05) treatment and time effect for glucose, with C being higher than PL. Interaction effects were observed for insulin and lactate. An increase in TE (min) at 100% VO2max was observed in the C versus PL trial (6.3 ± 3.4 vs. 4.4 ± 2.9, p < .001). A MRB+C may benefit cyclists due to increased BG and improved exercise performance.